Marbles and smartphone on physics laboratory: an investigation for finding coefficient of restitution. Issue 2 (June 2021) - Dahnuss, D; Marwoto, P; Iswari, R S; Listiaji, P
Abstract: Experimenting is a basic skill that science students must have. Experimental activities are generally carried out in the laboratory. But by using a smartphone, many experiments can be done outside the laboratory. This research is an example of an experiment using a smartphone that can be carried out outside the laboratory. This study aims to measure the coefficient of marbles restitution through a simple experiment assisted by a smartphone. Marbles are dropped from a certain height, the Phyphox application on a smartphone will record experimental data through a sound sensor. Experimental data recorded through a smartphone is used to analyze the coefficient of restitution and mechanical energy of marble during a collision with the floor. The experimental results show that smartphones can be used to determine the coefficient of restitution and mechanical energy as an experimental tool. We hope that this experiment will be an alternative method for lecturers or physics teachers to demonstrate bouncing objects to determine the coefficient of restitution and mechanical energy loss.